2008
DOI: 10.1089/ees.2006.0037
|View full text |Cite
|
Sign up to set email alerts
|

Recycling and Application Characteristics of Fly Ash from Municipal Solid Waste Incinerator Blended with Polyurethane Foam

Abstract: In this study, different fractions of fly ashes, poly (tetramethylene glycol) (PTMG), and excess 4, 4Ј-diphenylmethane diisocyanate (MDI) were added into a reactor to form the polyurethane (PU)/fly ashes blend. It is evident that heavy metals can be encapsulated in PU foam, which was shown by the results of a toxicity characteristic leaching procedure (TCLP) test. After the tensile strength test, the elongation test, and the hardness test, the physical and chemical properties of the PU/fly ashes blend were acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…It was reported that the incorporation of FA particles in PU foam dramatically increased the fire resistance and thermal stability of the composite foams. Choew et al [21] reported the usage of PU foam/FA blends as a commercial product to encapsulate heavy metals. It was observed that PU foam-FA blends were waterproof, with good resistance to heat and light.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the incorporation of FA particles in PU foam dramatically increased the fire resistance and thermal stability of the composite foams. Choew et al [21] reported the usage of PU foam/FA blends as a commercial product to encapsulate heavy metals. It was observed that PU foam-FA blends were waterproof, with good resistance to heat and light.…”
Section: Introductionmentioning
confidence: 99%
“…Rice, wheat straw, soybean, kraft lignin, solvolysis lignin, bagasse, molasses, wood flour, unmodified bark, modified corn starch, coffee powder, used and unused wood, starch, modified starch, bark, grain, used paper, cotton, and wheat stalks have been used to produce different types of polyurethane foams through a liquefaction process (Timothy & Glasser, 1984;Shiraishi et al, 1985;Hirose et al, 1989;Kennedy et al, 1993;Shiraishi et al, 1993;Meikleham & Pizzi, 1994;Alma et al, 1995;Alma, 1996a, Alma et al, 1996b, Alma et al, 1996cGe & Sakai, 1996;Alma, 1997;Alfani et al, 1998;Chian & Gan 1998;Ge & Sakai 1998;Alma & Kelley, 2000;Ge et al, 2000;Alma et al, 2002;Alma et al, 2003;Cuningham et al, 2003;Alma, 2005;Banik & Sain, 2008;Chow et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the reuse and recycling of industrial solid wastes and municipal solid wastes have attracted substantial interest in Taiwan (Chiang et al, 2010;Chow et al, 2008;Ghosh and Ghosh, 2013;Lin et al, 2009Lin et al, , 2011Popovici et al, 2013). According to Taiwan's Environmental Production Administration (EPA), 0.75 million tons of garbage was disposed in 2006, 5.84% of which was waste glass (Lin, 2007).…”
Section: Introductionmentioning
confidence: 99%